2016
DOI: 10.21475/ajcs.2016.10.09.p7825
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of extensive positive selection acting on cherry (Prunus avium L.) resistance gene analogs (RGAs)

Abstract: The cherry tree (Prunus avium L.), is an important tree species which is intensively plagued by many phytopathogenic fungal species. Resistance gene analogs (RGAs) are the largest class of resistance (R) genes and are pivotal components at breeding projects, serving as useful functional markers linked to R genes. In order to assess the evolutionary pressures acting upon P. avium RGAs candidates, their 173 homologues that have previously been deposited in GenBank were mined. Their proteins were clustered accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Previously, comparative analyses of R genes at Rosaceae species revealed that the solvent-exposed amino acid residues of the LRRs domains were significantly variable with intensive positive selective pressures acting upon them (Perazzolli et al 2014). Similar results were also observed in a genome wide analysis of the RGA in cherry (Zambounis et al 2016). Such evidences are interpreted as an additional indication of the active involvement of these regions in fungal pathogens recognition pathways (Zambounis et al 2012b), which is accurately consistent with the host-pathogen co-evolution processes leading to acquisition of disease resistance specificities (Mondragón-Palomino et al 2002).…”
Section: Resultssupporting
confidence: 68%
“…Previously, comparative analyses of R genes at Rosaceae species revealed that the solvent-exposed amino acid residues of the LRRs domains were significantly variable with intensive positive selective pressures acting upon them (Perazzolli et al 2014). Similar results were also observed in a genome wide analysis of the RGA in cherry (Zambounis et al 2016). Such evidences are interpreted as an additional indication of the active involvement of these regions in fungal pathogens recognition pathways (Zambounis et al 2012b), which is accurately consistent with the host-pathogen co-evolution processes leading to acquisition of disease resistance specificities (Mondragón-Palomino et al 2002).…”
Section: Resultssupporting
confidence: 68%
“…The ETI system activates complex plant immune reactions for defence against pathogens (Win et al 2012;Zhang et al 2017a). Plant defence mechanisms are constantly evolving to early respond against new diseases (Whitham et al 2016;Zambounis et al 2016). However, adaptation of pathogens to altering environment conditions happens quite faster than in plants.…”
Section: Ge For Improved Disease Resistancementioning
confidence: 99%
“…Plant defence mechanisms are constantly evolving to respond on time against new diseases-causing treats (Zambounis et al 2016a), such as evolving pathogen isolates and climate changes (Whitham et al 2016). Climate change alters dramatically the susceptibility of the plant host, and unfortunately, adaptation of pathogen genome to new environment progresses happens faster than in plant genome in a given pathosystem.…”
Section: Genomics Approaches For Disease Resistance Selection In Sweet Cherrymentioning
confidence: 99%
“…Therefore, increasing resistance to the major diseases by deciphering the genetic basis of resistance and subsequently creating genotypes with durable disease resistance is one of the basic prerequisites of sweet cherry breeders in the upcoming changes in climate. As a consequence, the assessment of disease resistance in cherry breeding germplasm is a prerequisite in terms of maintaining and enhancing the utility, durability and acceptance of new cultivars, besides the establishment of disease management strategies (Zambounis et al 2016a). Despite that this procedure is rather a time-consuming approach, previous studies have evaluated continuously the resistance of sweet cherry cultivars to economically important pathogens including the causal agents of powdery mildew and bacterial canker (Olmstead and Lang 2002;Mgbechi-Ezeri et al 2017).…”
Section: Genomics Approaches For Disease Resistance Selection In Sweet Cherrymentioning
confidence: 99%
See 1 more Smart Citation